(untitled) (Comprehensive Journal of Science, 2025)
Divorce for harm is considered one of the most serious forms of divorce, as it reflects the breakdown of family bonds due to the physical or psychological abuse or neglect suffered by one of the spouses, which makes the continuation of marital life impossible. The family represents the fundamental nucleus of society, and when this nucleus collapses as a result of injustice, neglect, or mistreatment, the consequences are not limited to the spouses alone but extend primarily to the children and then to society as a whole. Children are the most affected by divorce for harm, as they lose their sense of security and family stability and face psychological and behavioral problems that may accompany them throughout their lives, such as poor academic achievement, anxiety, depression, and delinquency. Society is also impacted by the increasing rates of family disintegration, which lead to higher levels of deviance, crime, the spread of armed groups, and the decline of moral values. Therefore, studying divorce for harm and its negative effects is an urgent necessity in order to understand the dimensions of divorce and to work toward limiting the spread of this phenomenon in recent times.